2017
DOI: 10.1038/cti.2017.7
|View full text |Cite
|
Sign up to set email alerts
|

Control of immune cell entry through the tumour vasculature: a missing link in optimising melanoma immunotherapy?

Abstract: Metastatic melanoma remains a fatal disease to many worldwide, even after the breakthrough introduction of targeted therapies such as BRAF inhibitors and immune checkpoint blockade therapies such as CTLA-4 and PD-1 inhibitors. With advances in our understanding of this disease, as well as the increasing data gathered from patient studies, the significance of the host immune response to cancer progression and response to treatment is becoming clear. More specifically, the presence of intratumoral CD8+ cytotoxic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 102 publications
(183 reference statements)
1
26
0
Order By: Relevance
“…Similarly, a higher immune score was associated with a longer survival time in melanoma and ovarian cancer, but earlier recurrence in hepatocellular carcinoma-adjacent tissue. The degree of tumour-infiltrating lymphocytes in particular activated CD8+ T-cells, within melanoma positively correlates with better prognosis ( 26 ). The decreased recruitment of tumor-infiltrating lymphocytes may lead to poor prognosis in high-risk ovarian cancer patients ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a higher immune score was associated with a longer survival time in melanoma and ovarian cancer, but earlier recurrence in hepatocellular carcinoma-adjacent tissue. The degree of tumour-infiltrating lymphocytes in particular activated CD8+ T-cells, within melanoma positively correlates with better prognosis ( 26 ). The decreased recruitment of tumor-infiltrating lymphocytes may lead to poor prognosis in high-risk ovarian cancer patients ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, using a dual tumor model we surprisingly found that synergy was achieved more effectively with anti-CTLA-4, rather than anti-PD-1. As anti-CTLA-4 promotes entry of new T cells into the tumor in addition to CD4 + and CD8 + T cell activation, whereas anti-PD-1 targets mainly rejuvenation of exhausted CD8 + T cells, [41][42][43][44] it may be possible that anti-CTLA-4 synergizes by promoting entry of the endogenous vaccine-induced T cells into the small untreated contralateral tumors, which may not have recruited or induced their own T cells. Another explanation could be that there is limited expression of PD-L1 in the untreated contralateral tumors, making blockade of the PD-1/PD-L1 axis less critical.…”
Section: Discussionmentioning
confidence: 99%
“…This requires cell-cell interactions via adhesion molecules such as selectin and integrin. Immune cells first undergo “rolling,” which is initiated by interactions between endothelial P/E-selectins, PNAd, and MAdCAM-1, as well as leukocyte L-selectin, PSGL-1, and E-selectin ligand 5 (Fig. 1 ).…”
Section: Introductionmentioning
confidence: 99%